Human papillomavirus and the three group metaphase figure as markers of an increased risk for the development of cervical carcinoma. - Claas, E. C. (1992)
In this study, the presence of atypical mitotic figures and human papilloma virus (HPV) genomes was related to the degree of cervical intraepithelial neoplasia (CIN) or microinvasive carcinoma (MIC) as found in 94 paraffin-embedded biopsies from cervical lesions. The results showed that the frequency of three group metaphase (TGM) figures, a special kind of atypical mitotic figure, as well as the presence of HPV 16 and 18 genomes increased with the degree of cervical intraepithelial neoplasia. TGM figures were observed in 24% of CIN2, up to 61% in CIN3 lesions, and in 83% of the microinvasive cervical carcinomas. HPV genomes were detected in 15% of CIN1, up to 75% in CIN3 lesions, and in 92% of the invasive carcinomas of the cervix. The combination of these two markers showed even a better association with a higher degree of cervical intraepithelial neoplasia. The results of these studies suggest that detection of particular HPV types, mainly HPV 16 and 18, and the presence of TGM figures can be considered as markers that indicate an increased risk for progression of cervical intraepithelial neoplasia to invasive carcinoma.